Використання методів гнучкої ендоскопії з можливістю керування у функціональній ендоскопічній ринохірургії - Сокольцов, А. О. (ХНУРЕ, 2024)
This work is devoted to examines the impact of chronic rhinosinusitis on social functioning and healthcare costs, emphasizing the importance of endoscopic technologies in surgical treatment. The study compares the effectiveness of new devices such as the Peregrine Drivable ENT Scope and EndoCAMeleon with traditional endoscopes. The advantages and disadvantages of each device are noted, as well as the prospects for their application in clinical practice to improve treatment outcomes for patients with chronic rhinosinusitis
Keywords: біомедицина; ринохірургія; гнучка ендоскопія